Phyllomedusa : journal of neotropical herpetology - Universidade de São Paulo. Departamento de Ciências Biológicas; Escola Superior de Agricultura "Luiz de Queiroz" (Melopsittacus Publicações Cientif́icas, 2002)
PHYLLOMEDUSA publishes original research articles, short communications and review papers concerning the whole field of Herpetology. PHYLLOMEDUSA also maintains sections for Book Reviews. Manuscripts will be considered on condition that they have not been published elsewhere or are not under consideration for publication, in whole or in part, in another journal or book. Publication in PHYLLOMEDUSA, including color pictures, is free of charge. All manuscripts are subject to peer review. This process averages 90 days. Authors receive pdf proofs before publication and 30 reprints free of charge. Full-text pdf versions of all articles are available for free download in this homepage.
Keywords: Herpetology : Periodicals; Reptiles : Periodicals; Amphibians : Periodicals; Amphibians; Herpetology; Reptiles; Brazil; Latin America